If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation. 15x βˆ’ y = βˆ’6 5x βˆ’ 3y = βˆ’13 5(βˆ’15x βˆ’ 6) βˆ’ 3y = βˆ’13 5(15x + 6) βˆ’ 3y = βˆ’13 5x βˆ’ 3(15x + 6) = βˆ’13 5x βˆ’ 3(βˆ’15x βˆ’ 6) = βˆ’13

Respuesta :

15x - y = - 6.....15x + 6 = y...so we sub in 15x + 6 in for y on the other equation

5x - 3y = -13
5x - 3(15x + 6) = -13 <== the new equation

Answer:

Hence, the resultant equation will be:

5x βˆ’3(15x + 6) = βˆ’13

Step-by-step explanation:

We are given a system of linear equations such that the first equation is given by:

15x βˆ’ y = βˆ’6------(1)

and the second equation is given by:

5x βˆ’ 3y = βˆ’13----------(2)

If you were to use the substitution method to solve the following system the new equation after the expression equivalent to y from the first equation is substituted into the second equation will be given by:

consider equation (1)

15x βˆ’ y = βˆ’6------(1)

find the expression in terms of x.

i.e. 15x+6=y---(A)

substitute this equation into equation (2) to obtain:

5x βˆ’ 3(15x + 6) = βˆ’13